Promoting collaboration between local community and park management towards sustainable outdoor recreation - Abdul Gani, Arni; Awang, Khairil Wahidin (Elsevier, 2013)
Outdoor recreation has existed since the first creation of parks in North America. Recreation involves many kinds of activities, may incorporate traditional beliefs and provides physical challenge. At the same time, being engage in outdoor recreation could provoke interest of the natural world. Engaging in outdoor recreation has greatly contributed towards better physical, mental and spiritual health of individuals. It also strengthens family bonds and instils pride in one's heritage. In addition, many parks and recreation areas are now often regarded as attractions to tourists. However, increase recreational use can have significant effect on land where it can lead to ecological and socio cultural impacts of an area. Damage to natural settings, degradation of environment and conflicts between users of the park are some of the common problems associated with poor planning and management of recreation activities in parks. These problems have existed for many years and researches have come up with measures to deal these with. Apart from that, sustainability rise as a concern for many parks and becomes imperative to ensure the continuous success of the park. Researchers have argued and agreed that park planning will require significant and structural changes in the future, where it is suggested that planning process should be based on dialogue and social learning between the management and local community. For park planning and management, this would mean new ways of approaching issues such as through collaborative action and consensus building. This conceptual paper discusses on the planning and management of outdoor recreation towards sustainable outdoor recreation. In addition, it also discusses on the type of planning theory to promote community and park management collaboration in outdoor recreation management.